2014
DOI: 10.1007/s00167-013-2830-3
|View full text |Cite
|
Sign up to set email alerts
|

Autologous collagen-induced chondrogenesis technique (ACIC) for the treatment of chondral lesions of the talus

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…As mentioned above, atelocollagen not only acts as a scaffold, but it also promotes osteoblast differentiation and type I collagen production [Kagawa et al, 2012]. Therefore, it has been used to treat fractures, articular defects, and soft tissue damage, and positive clinical results have been reported [Kagawa et al, 2012;Volpi et al, 2014;Kim et al, 2015]. As it is a gel, it can be applied to small defects or to fracture lines that cannot be filled by bone grafts or solid scaffolds, and it remains in the injected area because of its viscosity [Chaipinyo et al, 2004;Mimura et al, 2008;Jeong et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, atelocollagen not only acts as a scaffold, but it also promotes osteoblast differentiation and type I collagen production [Kagawa et al, 2012]. Therefore, it has been used to treat fractures, articular defects, and soft tissue damage, and positive clinical results have been reported [Kagawa et al, 2012;Volpi et al, 2014;Kim et al, 2015]. As it is a gel, it can be applied to small defects or to fracture lines that cannot be filled by bone grafts or solid scaffolds, and it remains in the injected area because of its viscosity [Chaipinyo et al, 2004;Mimura et al, 2008;Jeong et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that because atelocollagen consists of collagen fibrils and has little antigenicity, it acts as a scaffold for bone growth and also promotes osteoblast differentiation and type I collagen production [Hanai et al, 2012;Kagawa et al, 2012]. Some studies have reported clinical trials in which atelocollagen was used to treat cartilage defects [Kim et al, 2009;Volpi et al, 2014]. However, to the best of our knowledge, there have been few reports of atelocollagen application in cases of nonunion or delayed union with or without bone marrow aspirate concentrate (BMAC).…”
Section: Introductionmentioning
confidence: 99%
“…in this context, matrixassisted bone marrow stimulation is one of the most innovative techniques for the treatment of osteochondral lesions, allowing a one-step surgical treatment. the matrices used in this kind of application are usually made from components of the cartilage extracellular matrix, in particular hyaluronic acid and collagen, in order to provide mesenchymal stem cells with a microenvironment conducive to the achievement of an effective cartilage regeneration process (20)(21)(22). these procedures are often performed with an open approach; they generally require malleolar osteotomies and extensive arthrotomy that may result in nonunion or malunion of the malleolus, ankle stiffness, and longer rehabilitation (23).…”
Section: J Ointsmentioning
confidence: 99%
“…these procedures are often performed with an open approach; they generally require malleolar osteotomies and extensive arthrotomy that may result in nonunion or malunion of the malleolus, ankle stiffness, and longer rehabilitation (23). the autologous collagen-induced chondrogenesis (ACiC) technique is used in association with injectable collagen filler and thus it allows the chondral and osteochondral defects to be treated completely arthroscopically (22,24). one such filler, Cartifill tM (Joint Biomaterials sas, Mestre, italy) is an injectable scaffold made of atelocollagen isolated from porcine dermis, and nutrients essential for the maintenance of mesenchymal cells; it creates a stable matrix that, covering the cartilage defect, can be colonized by cells deriving from microfractures of the subchondral bone.…”
Section: J Ointsmentioning
confidence: 99%
See 1 more Smart Citation